IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN DI SEKOLAH DASAR: TANTANGAN DAN SOLUSI - Natasya T; Femi Br Ginting; Wiwik Kurniyati; Akhmad Faisal Hidayat (STKIP Subang, 2025)
The Merdeka Curriculum, initiated by the Indonesian government, aims to enhance the quality of education by providing flexibility to schools, teachers, and students in the learning process. This article examines the implementation of the Merdeka Curriculum in primary schools, focusing on the challenges faced and potential solutions. This study employs a literature review approach to analyze policies, official guidelines, and related research. The findings indicate that although the curriculum offers flexibility, there are challenges in teacher readiness, facilities, and understanding its application. This article provides practical recommendations to address these challenges effectively.